Effects of median refuge island and flashing vertical sign on conspicuity and safety of unsignalized crosswalks. (January 2019) - Vignali, Valeria; Cuppi, Federico; Acerra, Ennia; Bichicchi, Arianna; Lantieri, Claudio; Simone, Andrea; Costa, Marco
Highlights: Conspicuity was enhanced and speed was lower after the interventions. First-fixation distance to the crosswalk was 44.7% higher after the interventions. Fixations to vertical sign increased after the installation of a flashing light. The median refuge island significantly lowered drivers' distraction. Abstract: Pedestrian crossings are critical points in terms of road safety because they tend to be characterized by high accident rates. Pedestrian safety at zebra crossings depends mainly on vehicles speed. In this study the effects of median refuge island and "Yield here to pedestrians" flashing vertical sign on pedestrian crossing conspicuity were assessed with a before–after analysis of both speed and visual behaviour of drivers approaching to crosswalks. The elements of the pedestrian crossing that were more salient and how drivers' visual behaviour was related to speed were assessed analysing drivers' eye movements. The intervention significantly increased the fixation time to the zebra markings and the addition of the flashing light increased conspicuity and fixation time to the vertical sign. The median refuge island was glanced by 60.7% of the drivers. Distance of first-fixation of the crosswalk increased by 44.7%. Notwithstanding mean and V85 speed parameters were lower after the intervention, the effects on crosswalk visual attention were higher than on speed.